Los principios UNIDROIT para los contratos internacionales (2002)
This paper expIains UNIDROIT principIes for international cornmercial contracts binding parties, when proper applicabIe ruIe of Iaw can not be established, in order to attain objective court sentence. To validate importance of UNIDROIT principIes, this study offers several sentences of the International Arbitrage Tribunal of the International Chamber of Cornrnerce, which refers to fuese principIes for judgernent.These principIes represent new approach to international business Iaw and are intended to rernedy Iaw flaws and, by the same rneans, fill gaps frorn Vienna Convention of 1980 on international trade of goods and services.Authors calls attention on urgent need to introduce studies on mechanisrns of Trade Contracts in our universities, worIdwide discussed but bareIy known in our region